Anisotropy of mechanical properties of oxide single crystals for inorganic scintillators - Babiychuk, I.P.; Baumer, V.N.; Bondar, V.G.; Grinyov, B.V.; Krivoshein, V.I.; Nagornaya, L.L.; Pirogov, E.N.; Ryzhikov, V.D. (Functional Materials, 2004)
Методом склерометрии исследована анизотропия микротвердости монокристаллов PbWO₄ CdWO₄ и Gd₂SiO₅ для определения возможного характера разрушения при механическом воздействии в процессе изготовления сцинтилляторов. The microhardness anisotropy of single crystalsPbWO₄ CdWO₄ and Gd₂SiO₅ by the method of sclerometry with the aim of determining possible character of destruction have been studied during mechanical processing in the course of preparation of scintillators. Методом склерометрії досліджєно анізотропію) мікротвєрдості мoнoкpиcтaлiв PbWO₄ CdWO₄ и Gd₂SiO₅ для визначення характеру руйнування кристалів при механічному впливі в процесі виготовлення сцинтиляторів.